2018
DOI: 10.1093/nar/gky254
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Rad1–Rad10 interactions with Msh2–Msh3, Saw1 and RPA is essential for functional 3′ non-homologous tail removal

Abstract: Double strand DNA break repair (DSBR) comprises multiple pathways. A subset of DSBR pathways, including single strand annealing, involve intermediates with 3′ non-homologous tails that must be removed to complete repair. In Saccharomyces cerevisiae, Rad1–Rad10 is the structure-specific endonuclease that cleaves the tails in 3′ non-homologous tail removal (3′ NHTR). Rad1–Rad10 is also an essential component of the nucleotide excision repair (NER) pathway. In both cases, Rad1–Rad10 requires protein partners for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…9), demonstrating that Saw1 was not required for Z-DNA-induced mutation. Since Saw1 is essential for Rad1 recruitment and cleavage at 3′ tailed recombination intermediates and 3′ NHTR 40,45 , this result suggested that the Rad1-10 complex was involved in Z-DNA processing in a pathway unique to that of 3′ NHTR. Furthermore, in the ChIP assays the primers were designed to amplify a region containing the Z-DNA-forming sequence so that a positive PCR amplification suggested that at least some of the ERCC1-XPF and MSH2-MSH3 complexes bound on the intact DNA, and not on 3′-tails generated from nicked DNA or DSBs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…9), demonstrating that Saw1 was not required for Z-DNA-induced mutation. Since Saw1 is essential for Rad1 recruitment and cleavage at 3′ tailed recombination intermediates and 3′ NHTR 40,45 , this result suggested that the Rad1-10 complex was involved in Z-DNA processing in a pathway unique to that of 3′ NHTR. Furthermore, in the ChIP assays the primers were designed to amplify a region containing the Z-DNA-forming sequence so that a positive PCR amplification suggested that at least some of the ERCC1-XPF and MSH2-MSH3 complexes bound on the intact DNA, and not on 3′-tails generated from nicked DNA or DSBs.…”
Section: Discussionmentioning
confidence: 97%
“…DNA polymerase and ligase fill and seal the gap only after the unannealed 3′-tails are removed. Eichmiller et al (2018) reported that the Msh2-Msh3 complex could bind to the 3′-free tail and then recruit Rad1-10 and Saw1 in yeast 45 . Saw1 can directly stimulate the endonuclease activity of Rad1-10 44 in processing the 3′-tails.…”
Section: Discussionmentioning
confidence: 99%
“…In triple-labeled experiments in which Saw1 was also fluorescently labeled, we observed Saw1 and Rad1-Rad10 frequently localized to the repair sites at the same time, in all flap substrates. Prior literature provided evidence for a Msh2-Msh3-Saw1-Rad1-Rad10 protein complex and other evidence suggesting that Msh2-Msh3 might stabilize the annealed repair intermediate thereby recruiting Saw1 and Rad1-Rad10 to the DSB site [ 9 , 19 ]. It is possible that Msh2-Msh3 is unable to distinguish between varying flap lengths and recruits Saw1 to all flap substrates regardless of necessity.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the relationship between the primary structure of this region of HsRAD52 and its ability to support SSA in budding yeast will be a subject of continued investigation. Additionally, the capacity of HsRAD52-FLAG to act as a replacement for ScRad52 in SSA suggests that it works in concert with other factors important for SSA in yeast [68][69][70][71][72][73][74][75][76], which will also be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%